The Integration of Green Shipping Technologies in the Management of International Freight - Tama Wirawan; Syaila Cendana Maharani (Indonesian Maritime Researchers and Lecturers, 2025)
The growing environmental concerns and regulatory pressures on the shipping industry have prompted a shift towards the integration of green shipping technologies in managing international freight. This research investigates the adoption and effectiveness of these technologies, focusing on their role in reducing emissions, improving fuel efficiency, and enhancing the sustainability of global logistics. The study employs a mixed-methods approach, combining qualitative interviews with industry experts and quantitative analysis of freight operations data. The findings suggest that while green shipping technologies offer significant environmental benefits, their widespread adoption is hindered by high initial costs and regulatory complexities. Despite these challenges, the integration of sustainable practices in international freight management presents a promising pathway for achieving long-term environmental goals and improving industry competitiveness. The study highlights the need for collaborative efforts between shipping companies, policymakers, and stakeholders to overcome barriers and facilitate the adoption of green shipping technologies.